Advancement in the Feeding and Nutrition of Farm Animals of Bangladesh and a Panoramic View 2050 - Khan Shahidul Huque; Nazmul Huda (Turkish Journal of Agriculture: Food Science and Technology)
This article describes genesis and the advances of schooling, research and extension of animal nutrition science and practices in Bangladesh. It portrays sine qua non of the advancement of animal nutrition, fodder production and frontier knowledge of allied disciplines. Domestic growth of good practices and its global and regional competitive advantages are delineated for supporting the growing need of safe animal sourced food pillared with profit, people, planet and the ethics of sustainable production of farm animals. A vision of becoming world middle income country with a national population plateau of around 202.0 million and demographic shifts by 2050 may require the annual production of 130.0 and 27.0 thousand tons of manufactured dairy and beef feed furthering global trading competitions for feed ingredients. This competition may be minimized through the production and supply of domestic sourced unique quality feeds and value additions to roughages. Capacity enhancement in research, education and extension will boost socioeconomic and the production efficiency of farm animals and enhance sustainable growth of feed industry racing with regional and global competitions.